Merging the Multi-Target Effects of Phytochemicals in Neurodegeneration: From Oxidative Stress to Protein Aggregation and Inflammation - Fiona Limanaqi; Francesca Biagioni; Federica Mastroiacovo; Maico Polzella; Gloria Lazzeri; Francesco Fornai (MDPI AG, 2020)
Wide experimental evidence has been provided in the last decade concerning the neuroprotective effects of phytochemicals in a variety of neurodegenerative disorders. Generally, the neuroprotective effects of bioactive compounds belonging to different phytochemical classes are attributed to antioxidant, anti-aggregation, and anti-inflammatory activity along with the restoration of mitochondrial homeostasis and targeting alterations of cell-clearing systems. Far from being independent, these multi-target effects represent interconnected events that are commonly implicated in the pathogenesis of most neurodegenerative diseases, independently of etiology, nosography, and the specific misfolded proteins being involved. Nonetheless, the increasing amount of data applying to a variety of neurodegenerative disorders joined with the multiple effects exerted by the wide variety of plant-derived neuroprotective agents may rather confound the reader. The present review is an attempt to provide a general guideline about the most relevant mechanisms through which naturally occurring agents may counteract neurodegeneration. With such an aim, we focus on some popular phytochemical classes and bioactive compounds as representative examples to design a sort of main highway aimed at deciphering the most relevant protective mechanisms which make phytochemicals potentially useful in counteracting neurodegeneration. In this frame, we emphasize the potential role of the cell-clearing machinery as a kernel in the antioxidant, anti-aggregation, anti-inflammatory, and mitochondrial protecting effects of phytochemicals.